A Microwell‐Assisted Multiaptamer Immunomagnetic Platform for Capture and Genetic Analysis of Circulating Tumor Cells. Issue 24 (22nd November 2018) - Dong, Zaizai; Tang, Chuanhao; Zhao, Libo; Xu, Jiachao; Wu, Yayun; Tang, Xiaojun; Zhou, Wei; He, Rongxiang; Zhao, Rong; Xu, Li; Zhang, Zhen; Fang, Xiaohong
Abstract: Detection of circulating tumor cells (CTCs) in peripheral blood is of paramount significance for cancer diagnosis, progress evaluation, and individualized therapy. However, the rareness and heterogeneity of CTCs introduces significant challenges in the capture of cancer cells as well as downstream genetic analysis. In this work, a microwell‐assisted multiaptamer immunomagnetic platform (MMAIP) is proposed for highly efficient capture of CTCs with minimum influence of heterogeneity. Assisted by a microwell chip, the purity of CTCs is greatly improved, thus meeting the requirement of downstream gene analysis. This is, as far as is known, the first aptamer based platform enabling mutation analysis of the captured CTCs from cancer patients, which will contribute to the practical application of aptamers in clinics. Abstract : A new and simple microwell‐assisted multiaptamer immunomagnetic platform is developed for the detection and gene analysis of circulating tumor cells (CTCs). Magnetic nanoparticles modified with the aptamers having high affinity to drug‐sensitive and drug‐resistant lung cancer cells are used to capture heterogeneous CTCs. Purity of CTCs is further improved by microwell chip for mutation analysis of CTCs from clinical samples.